Motivational techniques to develop and strengthen the inter-learning of the English language in the students of the 9th year of basic education of the Machala house school and Juan Henriquez Coello high schools in the city of Machala during the academic period of 2010 - 2011. - Martínez Peña, Bairon Alexander (2011)
The objective of this thesis is to determine how motivation influences students when they learn the English language , motivation is an important factor in the education field because it allows students to assets are in the process of mutual learning . The research work has enabled us to establish how students should be motivated for English classes . For this we have developed fun activities in order to help students to participate actively and dynamically and these activities allow them to improve and develop the four skills of English so how they learn in a relaxed and comfortable atmosphere.